2016
DOI: 10.1038/nature19343
|View full text |Cite
|
Sign up to set email alerts
|

Atomically engineered ferroic layers yield a room-temperature magnetoelectric multiferroic

Abstract: Materials that exhibit simultaneous order in their electric and magnetic ground states hold promise for use in next-generation memory devices in which electric fields control magnetism. Such materials are exceedingly rare, however, owing to competing requirements for displacive ferroelectricity and magnetism. Despite the recent identification of several new multiferroic materials and magnetoelectric coupling mechanisms, known single-phase multiferroics remain limited by antiferromagnetic or weak ferromagnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
203
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 301 publications
(225 citation statements)
references
References 51 publications
8
203
0
3
Order By: Relevance
“…10 Thus, it is of great importance to study experimentally the possibility of a direct domain coupling effect in h-LuFeO 3 , which is energy efficient and highly desirable for future applications. Meanwhile, the recent ME coupling study on h-LuFeO 3 /LuFe 2 O 4 superlattices 11 demonstrates the capability of electrical field control of magnetism near the room temperature, which indicates h-LuFeO 3 and its related compounds are promising for future applications. However, with little knowledge of the intrinsic ME coupling of hLuFeO 3 itself, a full understanding of the ME coupling in superlattices and other related materials is unrealistic.…”
Section: Introductionmentioning
confidence: 99%
“…10 Thus, it is of great importance to study experimentally the possibility of a direct domain coupling effect in h-LuFeO 3 , which is energy efficient and highly desirable for future applications. Meanwhile, the recent ME coupling study on h-LuFeO 3 /LuFe 2 O 4 superlattices 11 demonstrates the capability of electrical field control of magnetism near the room temperature, which indicates h-LuFeO 3 and its related compounds are promising for future applications. However, with little knowledge of the intrinsic ME coupling of hLuFeO 3 itself, a full understanding of the ME coupling in superlattices and other related materials is unrealistic.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] The spontaneous magnetization is along the c axis. Recent work demonstrated that a super-lattice structure of hexagonal LuFe-O materials are promising for realizing room temperature multiferroic materials with co-existing ferroelectricity and ferromagnetism, 21 a property that has potential application in energy-efficient information processing and storage 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The elucidation of the strain effect in h-LuFeO 3 is an important advancement of our understanding on the coupling between the lattice and the improper multiferroicity. It is essential to the recently demonstrated hexagonal-ferrite super-lattice structures that are promising for room-temperature multiferroicity 41 , since the structural distortions in the h-LuFeO 3 layers are responsible for the ferroelectricity. The experimental characterization of strain effect in h-LuFeO 3 , can potentially be extended to measure the electronic and magnetic properties, when additional probes (e.g.…”
mentioning
confidence: 99%